2015
DOI: 10.1108/ijppm-09-2014-0138
|View full text |Cite
|
Sign up to set email alerts
|

Major factors affecting contemporary Japanese business environment

Abstract: Purpose – The purpose of this paper is to investigate factors influencing contemporary Japanese business environment mainly in the field of strategic management and, therefore, having influence on corporate performance and its measurement in selected manufacturing companies located in Japan in respect to their key business perspectives focused on people, processes and systems, innovations, finance, social responsibility and ecology, and that in relation to ongoing economic crises and a fundamental transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This was also later observed by Blahova et al (2015). An Indian case in point is the automobile manufacturer Maruti which is an example of success in India of Japanese CVO.…”
Section: Customer Value Orientation (Cvo)synthesizing a Meta-philosophymentioning
confidence: 63%
See 3 more Smart Citations
“…This was also later observed by Blahova et al (2015). An Indian case in point is the automobile manufacturer Maruti which is an example of success in India of Japanese CVO.…”
Section: Customer Value Orientation (Cvo)synthesizing a Meta-philosophymentioning
confidence: 63%
“…Turpin recommended an enhanced competition to meet and exceed customer expectations, instanced by activities such as customer involvement in new product development. This was also later observed by Blahova et al (2015). An Indian case in point is the automobile manufacturer Maruti which is an example of success in India of Japanese CVO.…”
Section: Customer Value Orientationmentioning
confidence: 63%
See 2 more Smart Citations
“…The research identified six major trends (as well as a few minor ones) currently having an impact on the Japanese business environment in the following areas: reformulating strategic management principles, a reduced lifelong employment orientation and a change in traditional human resource management practices, raising labour force participation, female participation in management and improving education, the use of non-financial performance indicators, the restructuring of a large organization into smaller units and opening up to outside influences. This research was complemented by an additional study focused on the Japanese business environment in 2015 (Blahová et al , 2015) and the Chinese business environment in 2015 (Blahová, 2015). The author discovered that among emerging topics being discussed among practitioners as well as researchers are, for example, a change in traditional Chinese management that represents a blend of tradition and more recent global imperatives (i.e.…”
Section: Introductionmentioning
confidence: 99%